2019
DOI: 10.1101/589747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-talk between m6A and m1A regulators, YTHDF2 and ALKBH3 fine-tunes mRNA expression

Abstract: The recently re-discovered interest in N 6 -methyl adenosine (m6A) -one of more than a hundred modifications found on eukaryotic mRNA (known as epi-transcriptomic codes) -is currently one of the most topical areas in science. The m6A methylation impacts on all aspects of cellular RNA metabolism and several physiological processes. Although less abundant than the m6A epitranscriptomic mark, the m1A methylation has recently also attracted interest due to its dynamic nature in response to physiological changes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, they did not validate these observations experimentally. The recent study of Lao and Barron shared on bioRxiv indicated that GFP mRNA is decorated by m 1 A and m 6 A marks when expressed in Chinese hamster ovary cells (CHO-K1) [ 73 ]. They used a GFP reporter to tackle the interplay between various m 1 A and m 6 A readers and erasers in CHO-K1 cells [ 73 ].…”
Section: A and M 1 A Mrna Marks Are Recognized By The Same Readers Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they did not validate these observations experimentally. The recent study of Lao and Barron shared on bioRxiv indicated that GFP mRNA is decorated by m 1 A and m 6 A marks when expressed in Chinese hamster ovary cells (CHO-K1) [ 73 ]. They used a GFP reporter to tackle the interplay between various m 1 A and m 6 A readers and erasers in CHO-K1 cells [ 73 ].…”
Section: A and M 1 A Mrna Marks Are Recognized By The Same Readers Proteinsmentioning
confidence: 99%
“…The recent study of Lao and Barron shared on bioRxiv indicated that GFP mRNA is decorated by m 1 A and m 6 A marks when expressed in Chinese hamster ovary cells (CHO-K1) [ 73 ]. They used a GFP reporter to tackle the interplay between various m 1 A and m 6 A readers and erasers in CHO-K1 cells [ 73 ]. They observed that the well-established m 6 A reader YTHDF2 targets m 1 A sites and facilitates GFP mRNA destabilization.…”
Section: A and M 1 A Mrna Marks Are Recognized By The Same Readers Proteinsmentioning
confidence: 99%
“…On the other end, RBPs controlling the lifecycle of RNA modifications appear to interact with marks other than their canonical one. For instance, the YTHDF2 m 6 A reader may "integrate" epitranscriptomics marks by also reading m 1 A and m 5 C (Dai et al 2018b;Lao and Barron 2019;Seo and Kleiner 2020;Dai et al 2020). A conserved residue of YTHDF2 (Trp 432 ) is required for the recognition of all the three modifications, albeit the affinities for m 1 A and m 5 C are lower than those for m 6 A.…”
Section: Interplaymentioning
confidence: 99%